Aktivitas Antibakteri Ekstrak Etanol dan Etil Asetat Batang Tanaman Brotowali (Tinospora crispa, L. Miers) terhadap Bakteri Escherichia coli Enteropatogenik (EPEC) Penyebab Penyakit Diare - Fathmah, Ema Nuzula; Pujiyanto, Sri; Raharjo, Budi (Bioma : Berkala Ilmiah Biologi, 2019)
Diarrheal diseases is an endemic desease in Indonesia and potential desease of Kejadian Luar Biasa (KLB) which often leads to death. Enteropatogenic Escherichia coli (EPEC) is one of pathogenic bacteria which can cause diarrhea. Brotowali plant (Tinospora crispa, L. Miers) is one of traditional medicinal plants which is widely used to treat various diseases and and relatively have no side effects than chemical drugs. he purpose of this research is to know the antibacterial activity of Brotowali (Tinospora crispa, L. Miers) stems ethanol and ethyl acetate extract in inhibiting the growth of EPEC bacteria causing diarrheal disease. Brotowali extract was obtained by maceration method using ethanol and ethyl acetate solvent. The condensed extract obtained was dissolved in DMSO 100% until the concentration of the extract to 20%; 40% and 60%. Test of antibacterial activity used diffusion method using paperdisk. The ethanol and ethyl acetate extract of brotowali stems were each tested on EPEC bacteria. The results in this study are the inhibition zone on ethanol and ethyl acetate extract stem of brotowali plant to EPEC bacteria. The antibacterial activity of brotowali stem ethanol extract at 60% concentration showed the best effect compared to the concentration of 20% and 40%. The antibacterial activity of ethyl acetate extract of brotowali stem was as good at concentration of 20%; 40% and 60%. The antibacterial activity of brotowali stem ethyl acetate extract showed better results than brotowali stem ethanol extract